Evaluation of stirring rate and pH on phenolic compounds recovery from palm kernel shell heavy phase bio-oil - Wijayanti, Hesti; Mardina, Primata; Tuhuloula, Abubakar; Tri Ananda, Lidya; Aulia Rauf, Zahwa Syafa; Lutfi, Auliyani; Fadil Riyadi, Syahril (Communications in Science and Technology, 2023)
This study aims to develop an efficient separation method for phenolic compounds derived from the heavy phase of bio-oil produced by the pyrolysis of palm kernel shell. Two variables were investigated during phenolic compound extraction using dichloromethane, i.e., stirring rate and pH of the solution. In both variables, the composition, yield, and distribution coefficient of the extracted phase were investigated. The results showed that the phenolic compounds' extraction favors high stirring rate and it obtained more results at more acidic conditions (lower pH). The best conditions for phenolic compounds were at 300 rpm of stirring rate and pH 4, which resulted in 77.88 % of yield and a 1.13 distribution of coefficient for the total phenols. The findings of this research will contribute to the better separation of phenolic compounds in bio-oil for improving its fuel characteristics as well as producing value-added chemicals.